Summary of Hydrological modeling of sustainable land management interventions in the Mizewa watershed of the Blue Nile Basin - Schmidt, Emily; Zemadim, Birhanu (International Food Policy Research Institute, 2014)
This analysis utilizes recent hydrological and meteorological data collected from the Mizewa watershed in Fogera woreda in order to better understand the physical impact of sustainable land and watershed management (SLWM) investments. The effectiveness of the simulated conservation practices (terraces, bunds, and residue management) are evaluated using the Soil and Water Assessment Tool (SWAT) model taking into account investment decisions on different terrain types. Simulations compare the limited investments that currently exist with increases in terracing and residue management activities within the watershed. The results suggest mixed impacts on surface run-off and erosion depending on terrain and management practices. However, the type and amount of investment (and therefore costs) in SLWM have different implications with respect to labor input and utilization of agricultural land, and the consequent socio-economic effects on households.